2020
DOI: 10.17815/cd.2020.53
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Guidance by Colored Running Lights and Affordance: Route Choices of Adults and Older Children

Abstract: Guidance to emergency exits play an important role for safe evacuation. Dynamic route guidance by colored flashing lights and strobe lights at emergency exits has been tested [1–3], but the effects of dynamic lights to support route choices need to be determined in more detail. Also, the guidance effects of different colors need to be examined and the reaction of various groups of evacuees. The paper analyzes the effects of red and green running lights on route choice in subway stations comparing adults and ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…In English journalistic texts, green is relevant after black, while green and red share this position in German. We agree that green is associated with safety and rescue (Scheurmann & Karliczek, 2017) and redwith danger (Künzer et al, 2018). This fact proves, among other things, the use of these coloronyms in the texts of English-and German-language news about the zoning of countries during the pandemic.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In English journalistic texts, green is relevant after black, while green and red share this position in German. We agree that green is associated with safety and rescue (Scheurmann & Karliczek, 2017) and redwith danger (Künzer et al, 2018). This fact proves, among other things, the use of these coloronyms in the texts of English-and German-language news about the zoning of countries during the pandemic.…”
Section: Discussionsupporting
confidence: 53%
“…Instead, white is underused in the texts of journalistic discourse, because it, according to scholars (Spillmann, 2018), is perceived neutrally, and therefore cannot be information-rich. Künzer, Zinke and Hofinger (2018) argue that even the interaction of black and white is perceived neutrally. At the same time, the analysis of German journalistic texts showed that the coloronym weiß/white has a negative connotation in combination with nouns to denote racism, so it cannot be considered purely neutral.…”
Section: Discussionmentioning
confidence: 99%